Mechano-electric effect and a heart assist device in the synergistic model of cardiac function - Eun-jin Kim; Massimo Capoccia (Mathematical Biosciences and Engineering, 2020)
The breakdown of cardiac self-organization leads to heart diseases and failure, the number one cause of death worldwide. Within the traditional time-varying elastance model, cardiac self-organization and breakdown cannot be addressed due to its inability to incorporate the dynamics of various feedback mechanisms consistently. To face this challenge, we recently proposed a paradigm shift from the time-varying elastance concept to a synergistic model of cardiac function by integrating mechanical, electric and chemical activity on micro-scale sarcomere and macro-scale heart. In this paper, by using our synergistic model, we investigate the mechano-electric feedback (MEF) which is the effect of mechanical activities on electric activity—one of the important feedback loops in cardiac function. We show that the (dysfunction of) MEF leads to various forms of heart arrhythmias, for instance, causing the electric activity and left-ventricular volume and pressure to oscillate too fast, too slowly, or erratically through periodic doubling bifurcations or ectopic excitations of incommensurable frequencies. This can result in a pathological condition, reminiscent of dilated cardiomyopathy, where a heart cannot contract or relax properly, with an ineffective cardiac pumping and abnormal electric activities. This pathological condition is then shown to be improved by a heart assist device (an axial rotary pump) since the latter tends to increase the stroke volume and aortic pressure while inhibiting the progression (bifurcation) to such a pathological condition. These results highlight a nontrivial effect of a mechanical pump on the electric activity of the heart.